Validation of Pre-Operative BOEY’s Score for Post-Operative Outcomes of Duodenal Ulcer Perforation: A Study at a Tertiary Care Hospital in Khyber Pukhtunkhwa - Ejaz, Sonia; Abbas, Khalid; Rahman, Sara; Tayyeb, Muhammad; Shah, Suliman; Khalil, Mazhar; Zahoor, Sikandar (Indus Journal of Bioscience Research, 2025)
Introduction: The lifetime prevalence of peptic ulcer disease, once estimated to be 5-10%, has steadily declined over the past three decades. This study will not only report recent data for local and international practitioners but also serve as a validation of Boey’s score in our population. Objective: To assess the frequency of in-hospital morbidity and mortality following peptic ulcer perforation repair based on preoperative Boey’s score. Methods and Materials: A Descriptive Case series was conducted in Surgical B unit, Lady Reading Hospital, Peshawar, from January 2022 to December 2024. We conducted this study on 71 patients aged between 18 and 60 years, of both genders, with peptic ulcer perforation. The frequency of morbidity and mortality was assessed based on Boey’s score. Results: The mean age of the patients was 38.49 ± 11.59 years. The frequency of morbidity in patients with Boey’s score 0 was 1 (1.9%), with score 1 was 2 (50%), with score 2 was 5 (83.2%), and with score 3 was 8 (88.9%). The frequency of mortality in patients with Boey’s score 0 was 1 (1.9%), with score 1 was 1 (25%), with score 2 was 2 (33.3%), and score 3 was 4 (44.4%). Conclusion: From our study we conclude that based on preoperative Boey’s score 0, 1, 2 and 3 the frequency of morbidity was 1 (1.9%), 2 (50%), 5 (83.2%) and 8 (88.9%) respectively while mortality was 1 (1.9%), 1 (25%), 2 (33.3%) and 4 (44.4%) respectively following peptic ulcer perforation.